STUDI KROMOSOM IKAN BAUNG (Hemibagrus lacustrinus NG & KOTTELAT, 2013) FAMILI BAGRIDAE DI MATUR, SUMATERA BARAT - Yuliwan Saputra; Dewi Imelda Roesman; Syaifullah Syaifullah (Fakultas Perikanan dan Kelautan, Universitas Riau, 2017)
Chromosomal characteristics of catfish Hemibagrus lacustrinus, known as Baung fish, a new species of bagrid catfish from the upriver stream of Batang Sianok, West Sumatra, that recently described by Ng and Kottelat, 2013 was examined from the gills of 5 healthy specimens using general squash method. The result showed that diploid chromosome number of this species was 2n=56. Thekaryotype consisted of 28 metacentric (m), 10 submetacentric (sm), 8 subtelocentric (st) and 10 acrocentric (a) chromosomes. The chromosome formula can be represented as 2n= 28m+ 10sm+ 8st+ 10a. The largest chromosome in this species is a pair of submetacentric chromosomes and the smallest pair is acrocentric chromosomes. The present study is the first report on the karyology of this particular species and helping to support the karyotype data of the genus Hemibagrus. This study will also open for several future studies to explore this species.